Influence of shade on the growth of seedlings of three Amazon species - Campos, Moacir Alberto Assis; Uchida, Toshihiro (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this paper was to assess the development of Jacaranda copaia (Aubl.) D. Don., Hymenaea courbaril L. and Ochroma lagopus (Cav. ex. Lam.) Urban seedlings under different shade levels in the nursery. The experiment was carried out at Experimental Station of Tropical Silviculture (EEST) of Inpa, in Manaus, AM, Brazil. The experiment design was fully randomised blocks with five treatments: two treatments with 50% of shading during 15 and 30 days, respectively and the remaining period under full sun light (0%) and three treatments under 30, 50 and 70% shade, respectively by using black polypropylene screen. Stem diameter, seedling height, root length, leaf area, dry mass of leaves, root and stem, shoot/root ratio and height/diameter ratio were assessed. Hymenaea courbaril had its growth affected under 70% of shade. Ochroma lagopus and Jacaranda copaia seedlings increased their growth under shade, but seedlings quality was poor. In choosing shade levels to grow seedlings, shoot/root ratio and development of root system should be considered.